2021
DOI: 10.1136/jitc-2021-003480
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing cancer therapy via complementary mechanisms of immune activation: PD-1 blockade, neoantigen vaccination, and Tregs depletion

Abstract: BackgroundA number of different immune pathways are involved in the effective killing of cancer cells, collectively named as the ‘Cancer Immunity Cycle’. Anti-PD-1 checkpoint blockade (CPB) therapy is active on one of these pathways and reinvigorates anticancer T cell immunity, leading to long-term responses in a limited fraction of patients with cancer. We have previously shown that neoantigens-based adenovirus vectored vaccine in combination with anti-PD-1 further expands pre-existing anticancer immunity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…IL-2, the first cytokine approved for clinical cancer treatment, was restricted by the proliferation of Tregs expressing high-affinity IL-2Rα (CD25), which hindered anti-tumor immunity. Several structural variants of IL-2 without binding to IL2Rα have been developed, for example, Bempegaldesleukin (BEMPEG: NKTR-214) 169 and Neoleukin-2 (Neo2/15) 170 . A study found that neoantigen vaccination alone was ineffective, BEMPEG monotherapy cured 20% of the mice, and the combination led to tumor regression in half mice.…”
Section: Neoantigen Vaccine and Clinical Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-2, the first cytokine approved for clinical cancer treatment, was restricted by the proliferation of Tregs expressing high-affinity IL-2Rα (CD25), which hindered anti-tumor immunity. Several structural variants of IL-2 without binding to IL2Rα have been developed, for example, Bempegaldesleukin (BEMPEG: NKTR-214) 169 and Neoleukin-2 (Neo2/15) 170 . A study found that neoantigen vaccination alone was ineffective, BEMPEG monotherapy cured 20% of the mice, and the combination led to tumor regression in half mice.…”
Section: Neoantigen Vaccine and Clinical Applicationmentioning
confidence: 99%
“…A study found that neoantigen vaccination alone was ineffective, BEMPEG monotherapy cured 20% of the mice, and the combination led to tumor regression in half mice. These may be related to the increased level of vaccine-induced T cells and CD8+ T cells infiltration, and the reduced population of Tregs caused by BEMPEG 169 . Furthermore, TLR played an essential role in anti-infective immune responses.…”
Section: Neoantigen Vaccine and Clinical Applicationmentioning
confidence: 99%
“…It may also be associated with preexisting and acquired resistance mechanisms that impede T-cell functions and lead to tumor escape from the immune system [ 82 , 83 ]. To bypass resistance mechanisms, neoantigen-based vaccination was combined with the depletion of regulatory T cells (Tregs) in murine cancer models [ 84 ]. In this context, a combination of an IL-2 pathway agonist with Treg-depleting activity with the cancer vaccine led to the activation of neoantigen-specific T cells and a complete eradication of the tumor [ 84 ].…”
Section: Neoantigens As Promising Targets For Cancer Immunotherapymentioning
confidence: 99%
“…To bypass resistance mechanisms, neoantigen-based vaccination was combined with the depletion of regulatory T cells (Tregs) in murine cancer models [ 84 ]. In this context, a combination of an IL-2 pathway agonist with Treg-depleting activity with the cancer vaccine led to the activation of neoantigen-specific T cells and a complete eradication of the tumor [ 84 ]. With regard to the issue of the low frequency of neoantigen-specific T cells, engineered IL-2 receptor (IL-2R) agonists have been designed to expand T lymphocytes and take advantage of IL-2 benefits [ 85 ].…”
Section: Neoantigens As Promising Targets For Cancer Immunotherapymentioning
confidence: 99%
“…To this end, vaccine adjuvants were shown to play a fundamental role in increasing vaccine immunological potency and protection. This is achieved by combined administration of vaccine and immune-modulatory molecules, as it has been welldocumented, and found to have broad applications spanning from infectious diseases to cancer (5)(6)(7)(8)(9)(10). Classical vaccines can take advantage from the use of adjuvant compounds, such as aluminum salts, oil in water emulsion, and the more recently approved AS01, AS03, AS04, CpG ODN, and MF59, as a mean to improve magnitude and quality of antigen-specific adaptive immunity for optimized protection against pathogens (11,12).…”
Section: Introductionmentioning
confidence: 99%